Tecnología y analítica del aprendizaje: una revisión a la literatura - Contreras-Bravo, Leonardo-Emiro; Tarazona-Bermúdez, Giovanny-Mauricio; Rodríguez-Molano, José-Ignacio (Revista Científica, 2021)
Abstract A study concerning learning analytics is presented. This area consists of the collection and analysis of data generated by students and their iterations with the purpose of understanding and optimizing learning. By using databases, a referential review of the last five years is proposed to identify aspects related to the growth of this approach and its fields of application in higher education. The volume of related research is increasing due to the need to investigate more accurate predictive models and new algorithms in the field of data science.